1994
DOI: 10.1093/intimm/6.9.1345
|View full text |Cite
|
Sign up to set email alerts
|

The role of the conserved residue in pocket A and the polymorphic residue in pocket E of HLA-B*3501 in presentation of human minor histocompatibility peptides to T cells

Abstract: We investigated T cell recognition for human minor histocompatibility (hmH) peptides using HLA-B*3501 restricted, hmH specific cytotoxic T lymphocytes (CTL) clones. These CTL clones killed C1R cells expressing HLA-B*3501 but not C1R cells expressing chimeric antigens between HLA-B*3501 and HLA-B*5101. They also failed to kill C1R cells expressing HLA-B*3501 mutants at residue 152 (B*3501-V152E) or at residue 171 (B*3501-Y171H). The CTL clone failed to kill C1R cells expressing these mutant molecules loaded wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…T2 cells transfected with other individual HLA class I antigens were also used for MHC stabilization assays. T2 cells expressing HLA B35, B7, and B27 have been described elsewhere (44,46,53). T2 cells expressing HLA A3, A24, and B8 were established by transfecting expression vectors encoding individual class I alleles as described previously (24).…”
Section: Methodsmentioning
confidence: 99%
“…T2 cells transfected with other individual HLA class I antigens were also used for MHC stabilization assays. T2 cells expressing HLA B35, B7, and B27 have been described elsewhere (44,46,53). T2 cells expressing HLA A3, A24, and B8 were established by transfecting expression vectors encoding individual class I alleles as described previously (24).…”
Section: Methodsmentioning
confidence: 99%
“…27 T2 cells transfected with a number of different HLA alleles were kindly provided by Dr A McMichael, IMM, John Radcliffe Hospital, Oxford, UK (HLA-A*0301, -B*0702, -B*2705, -B*3501), and Dr M Masucci, MTC, Karolinska Institute, Stockholm, Sweden (HLA-A*1101). [28][29][30][31][32][33] The BM36.1 cell line is also defective in TAP function and has a similar phenotype as T2 with low expression of HLA class I (HLA-A*0101, HLA-B*3501) at the surface. 34 BM36.1 cells were kindly provided by Dr A Ziegler, Humboldt University, Berlin, Germany.…”
Section: Cell Linesmentioning
confidence: 99%
“…The T2.B35 cell line was derived by stable transfection of T2 cells with HLA B*3501. 13 Primary fibroblast cell lines were established from human foreskin fibroblasts. Immature monocyte-derived dendritic cells (MoDCs) were generated by plating peripheral blood mononuclear cells in 6-well plates for 90 minutes and treating the adherent monocytes with GM-CSF 1000 IU/mL and IL-4 1000 IU/mL (both from Schering-Plough) for 5 days.…”
mentioning
confidence: 99%
“…14 In characterizing its endogenous presentation, we found that the LPL epitope was not only efficiently processed and presented by TAP-positive primary fibroblasts but also by TAP-deficient T2.B35 cells ( Figure 1A), the latter being stable HLA-B*3501 transfectants derived from a TAP1 and TAP2 deficient B xT hybrid cell line known as T2 or 174xCEM.T2. 13,16 We next used chemical inhibitors to determine whether antigen processing in the 2 cell types used the same or distinct pathways. The LPL epitope sequence is predicted to be hydrophobic.…”
mentioning
confidence: 99%